Methyl-β-cyclodextrin restores impaired autophagy flux in Niemann-Pick C1-deficient cells through activation of AMPK. Issue 8 (3rd August 2017) - Dai, Sheng; Dulcey, Andrés E.; Hu, Xin; Wassif, Christopher A.; Porter, Forbes D.; Austin, Christopher P.; Ory, Daniel S.; Marugan, Juan; Zheng, Wei
ABSTRACT: The drug 2-hydroxypropyl-β-cyclodextrin (HPβCD) reduces lysosomal cholesterol accumulation in Niemann-Pick disease, type C (NPC) and has been advanced to human clinical trials. However, its mechanism of action for reducing cholesterol accumulation in NPC cells is uncertain and its molecular target is unknown. We found that methyl-β-cyclodextrin (MβCD), a potent analog of HPβCD, restored impaired macroautophagy/autophagy flux in Niemann-Pick disease, type C1 (NPC1) cells. This effect was mediated by a direct activation of AMP-activated protein kinase (AMPK), an upstream kinase in the autophagy pathway, through MβCD binding to its β-subunits. Knockdown of PRKAB1 or PRKAB2 (encoding the AMPK β1 or β2 subunit) expression and an AMPK inhibitor abolished MβCD-mediated reduction of cholesterol storage in NPC1 cells. The results demonstrate that AMPK is the molecular target of MβCD and its activation enhances autophagy flux, thereby mitigating cholesterol accumulation in NPC1 cells. The results identify AMPK as an attractive target for drug development to treat NPC.